What Works in the Field? Evaluating Informal Science Events - Grand, Ann; Sardo, Ana Margarida (Frontiers in Communication, 2017)
Around the world, increasing numbers of people are attending informal science events, often ones that are part of multi-event festivals that cross cultural boundaries. For the researchers who take part, and the organisers, evaluating the events’ success, value and effectiveness is hugely important. However, the use of traditional evaluation methods such as paper surveys and formal structured interviews poses problems in informal, dynamic contexts. In this article, we draw on our experience of evaluating events that literally took place in a field, and discuss evaluation methods we have found to be simple yet useful in such situations.